Produção e parâmetros de qualidade de leite e queijos de ovelhas Lacaune, Santa Inês e mestiças submetidas a dietas elaboradas com soja ou linhaça - Claudia Freire de Andrade Morais Penna (2011)
Sheep's milk production is increasing in Brazil, mainly in South and Southeast regions. Because this milk is much more concentrated than cow's, is usually processed into dairy products, especially in various types of cheese and yogurt in the world. However, research on sheep milk in Brazil are still scarce, so there is a need to know the characteristics of production and composition of the sheep milk, fed and managed under local conditions in order to give information for the improvement of the production indices and milk quality. Thus, experiments were conducted with the aim of: 1) compare the results of the sheep milk composition obtained in conventional analytical techniques and electronic equipment calibrated with bovine milk patterns, 2) evaluate the production and composition of sheep milk from genotypes Lacaune, Santa Inês and crossbred between these breeds, 3) know theeffects of two concentrates, formulated with soybean seed or linseed on production and chemical composition of sheep milk and 4) evaluate the cheese yield of sheep milk produced by these genotypes and fed with these diets, and the acceptance of cheese, knowing the market potential that they offer. The sheep were kept on a farm and managed according to the specific instructions for feeding and management inherent in the experiment. In the study about the use of Bentley2000®, the correlations obtained between the values read to the equipment and conventional methods were above 90% for all parameters studied, with no significant variations in the results (P>0.05). Regarding the genotypes, the Santa Inês ewes showed the lowest milk production (438.78 mL/day), and the crossbred F1 showed the largest production (1041.82 mL/day), followed by F2 (985.61 mL/days) and Lacaune (853.83 mL/day) (P<0.05). There were differences in milk composition according to genotypes (P<0.05). The production of sheep was higher when fed with soybean compared to flaxseed (P<0.05), and affected the composition of milk in a few parameters, but differently among the genotypes. There were differences (P<0.05) in cheese yield between genotypes, being higher for Santa Inês ewes' milk (4.17 Lkg-1) and similar between the Lacaune (5.17 Lkg-1) and crossbreds F1 and F2 (4.65 and 4.77 Lkg-1, respectively). The diet of sheep affected the acceptance of cheese, favoring the use of soybean (P<0.05) but did not alter the intent of consumption of processed cheese from sheep's milk (P>0.05), which was relatively high, with acceptance rates above 70%. According to results, it was observed that the use of equipment Bentley 2000® calibrated with cows milk is feasible, giving reliable results for fat, protein and total solids of milk. It was concluded that Santa Inês ewes showed moderate potential for milk production and, in general, the introduction of Lacaune in farms of Santa Inês ewes canbe beneficial because it promotes increased milk production. In addition, the milk of this genotype proved to be very rich in constituents, making it ideal for processing into cheese, which showed good acceptance by the panelists, indicating good potenti al for sale in themarket and can allow the diversification of activities in farms, increasing the income of farmers with dairy production